1994 IEEE MTT-S International Microwave Symposium Digest (Cat. No.94CH3389-4)
DOI: 10.1109/mwsym.1994.335231
|View full text |Cite
|
Sign up to set email alerts
|

Reliability study on pseudomorphic InGaAs power HEMT devices at 60 GHz

Abstract: Two-temperature RF-stressed acceluated life test on discrete pseudomorphic InGaAs power HEMT devices at 60 GHz shows a failure mode with an activation energy of 1.6 eV. The projected mean time-to-failure of 1 E7 hours at 125 OC channel temperature indicates that this device technology can be highly reliable for critical applications at millimeter-wave frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…High channel temperature not only degrades the device characteristics but also decreases the device lifetime. Experimental proofs have been observed for InGaAs MHEMTs [4][5][6][7], and the importance of the long-term stability of MHEMTs has been reported by several research groups [8][9][10][11][12]. It was reported that high channel temperature accelerated degradation processes in MHEMTs, such as gate sinking, ohmic contact degradation, hot electron issues, etc 3 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…High channel temperature not only degrades the device characteristics but also decreases the device lifetime. Experimental proofs have been observed for InGaAs MHEMTs [4][5][6][7], and the importance of the long-term stability of MHEMTs has been reported by several research groups [8][9][10][11][12]. It was reported that high channel temperature accelerated degradation processes in MHEMTs, such as gate sinking, ohmic contact degradation, hot electron issues, etc 3 Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%